2012
DOI: 10.1105/tpc.112.101915
|View full text |Cite
|
Sign up to set email alerts
|

The Phytochrome-Interacting VASCULAR PLANT ONE–ZINC FINGER1 and VOZ2 Redundantly Regulate Flowering in Arabidopsis

Abstract: The timing of the transition to flowering in plants is regulated by various environmental factors, including daylength and light quality. Although the red/far-red photoreceptor phytochrome B (phyB) represses flowering by indirectly regulating the expression of a key flowering regulator, FLOWERING LOCUS T (FT), the mechanism of phyB signaling for flowering is largely unknown. Here, we identified two Arabidopsis thaliana genes, VASCULAR PLANT ONE-ZINC FINGER1 (VOZ1) and VOZ2, which are highly conserved throughou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
166
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(187 citation statements)
references
References 96 publications
14
166
0
7
Order By: Relevance
“…17 Although the green fluorescent protein-fused VOZ2 signal was predominantly observed in the cytoplasm under normal growth conditions, nuclear-localization-signalcontaining but not nuclear-export-signal-containing VOZ2 protein can complement the late-flowering phenotype of the voz1voz2 double mutant, indicating that VOZ proteins relocate from the cytoplasm to the nucleus and regulate the flowering signaling pathways. 16 Nonetheless, no clear nuclear localization of VOZ proteins under normal growth conditions has been observed in Arabidopsis, these data indicate possible transcriptional regulatory function of VOZ proteins under particular growth conditions.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…17 Although the green fluorescent protein-fused VOZ2 signal was predominantly observed in the cytoplasm under normal growth conditions, nuclear-localization-signalcontaining but not nuclear-export-signal-containing VOZ2 protein can complement the late-flowering phenotype of the voz1voz2 double mutant, indicating that VOZ proteins relocate from the cytoplasm to the nucleus and regulate the flowering signaling pathways. 16 Nonetheless, no clear nuclear localization of VOZ proteins under normal growth conditions has been observed in Arabidopsis, these data indicate possible transcriptional regulatory function of VOZ proteins under particular growth conditions.…”
Section: Introductionmentioning
confidence: 77%
“…Yasui et al also reported that nuclear localization signal-containing but not nuclear export signal-containing VOZ2 protein could complement the late-flowering phenotype of the voz1voz2 double mutant, indicating that VOZ proteins function in the nucleus for regulation of flowering. 16 We previously reported that VOZ2 is degraded by the ubiquitin-proteasome system under cold-stress conditions. 17 These results suggest that VOZ proteins are transferred to the nucleus and function as transcriptional regulators when the plant cells perceive certain environmental signals (e.g., light, cold or heat), and then are rapidly subjected to the ubiquitin/proteasome-dependent degradation for inactivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Light signals from multiple photoreceptors are integrated into the flowering pathway consisting of key factors, such as CO, FT, TWIN SISTER OF FT (TSF), SOC1, and FLOWERING LOCUS C (FLC) (8,21,22,(28)(29)(30). In the early-flowering phyB mutant, expression of FT, TSF, and SOC1 is increased (9,22).…”
Section: Significancementioning
confidence: 99%
“…Contrary to red light's role in CO protein stabilization, VASCU-LAR PLANT ONE ZINC FINGER 1 (VOZ1: At1g28520) and VOZ2 (At2g42400), two NAC (NAM, ATAF1/2 and CUC2) domain transcription factors, activate FT expression under long day conditions (Yasui et al, 2012). VOZ proteins interact with PHYB, and like PHYB, their movement between the cytoplasm and the nucleus is tightly regulated.…”
Section: Light Dependent Regulation Of Ft Transcriptionmentioning
confidence: 99%